The effect of the magnitude of weight loss on non-alcoholic fatty liver disease: a systematic review and meta-analysis - Koutoukidis, DA; Koshiaris, C; Henry, JA; Noreik, M; Morris, E; Manoharan, I; Tudor, K; Bodenham, E; Dunnigan, A; Jebb, SA; Aveyard, P (Elsevier, 2020)
Background Trials show that weight loss interventions improve biomarkers of non-alcoholic fatty liver disease (NAFLD), but it is unclear if a dose-response relationship exists.